Strategi Pengembangan Desa Wisata Di Desa Sidorejo Kecamatan Kendal Kabupaten Ngawi - Murti, Endang (Universitas Merdeka Madiun, 2021)
Abstractâ€” The purpose of this study was to determine the strategy for developing a tourism village in Sidorejo Village, Kendal District, Ngawi Regency. Respondents or informants in this study were the Ngawi District Tourism Office, Sidorejo Village Nature Tourism Object Manager, Sidorejo Village Government Apparatus and tourists visiting the natural and earth tourism objects of Sidorejo Village. Data collection techniques used questionnaires and interviews and documentation. Data analysis techniques using SWOT analysis. The conclusion of the study shows that the strategy for developing natural attractions and camping ground in Sidorejo Village, Kendal District, Ngawi Regency includes: (1) Building infrastructure such as access roads to tourist sites that are easier to reach using private vehicles or public transportation and the roads are already physically paved. ; (2) Creating tourist attractions such as dance, music and traditional ceremonies of a local culture, both traditional and modern; (3) Promotion of tourism objects by giving free tickets to tourists; and (4) Developing tourism products by providing cafes around tourist objects and building hotels, guest houses, home stays and providing stalls for selling souvenirs in the form of traditional souvenirs and handicrafts.Â Keywordsâ€”: strategy; development; tourism village.